2014
DOI: 10.11604/pamj.2014.19.149.4010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of stress in Casablanca medical students: a cross-sectional study

Abstract: IntroductionRecently, an important literature data has reported that medical students experience stress more than students in other disciplines. In contrast, there is a significant shortage of the stress impact on the academic performance. The primary purpose of our study was to determine the prevalence of stress among Casablanca Medical students and to investigate if there is an association between stress and academic skills.MethodsA total of 275 participants studying at Casablanca Medical School were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 24 publications
1
20
1
1
Order By: Relevance
“…The highest prevalence of perceived high stress, 58.2% was found among the 5 th year medical students and closely followed by students in the final year class, 58.1%. This finding is similar to that found among medical students in Casablanca, Morocco where the highest prevalence of stress was among the fifth year medical students [26]. In a similar study in Abraka, Nigeria, students in the fourth year had the highest proportion of students who were stressed [27].…”
Section: Discussionsupporting
confidence: 86%
“…The highest prevalence of perceived high stress, 58.2% was found among the 5 th year medical students and closely followed by students in the final year class, 58.1%. This finding is similar to that found among medical students in Casablanca, Morocco where the highest prevalence of stress was among the fifth year medical students [26]. In a similar study in Abraka, Nigeria, students in the fourth year had the highest proportion of students who were stressed [27].…”
Section: Discussionsupporting
confidence: 86%
“…30,31 The most common perceived sources of academic stress, reported by various medical students in the literature, include fear of examinations, concerns about examination results and grades, and fear of failing the course at the end of the semester/year. [32][33][34] The flipped exam model in our study did not just reduce test anxiety, however it also addressed academic and test competence issues, which also represent substantial components associated with academic performance. 31 For instance, academic competence, which refers to a students' ability to manage their study load, 31 was undertaken by allowing the students to employ their understanding of the workshop presentations to design one question that they perceive as essential and relevant to learning.…”
Section: A J P E a C C E P T E D D R A F Tmentioning
confidence: 86%
“…Somehow weather changes, homesickness, lack of contact with family, pressure of studies, bullying and cadaveric dissection were all identified as environmental factors associated with stress among medical student in a study that was conducted at medical college in Islamabad, Pakistan (16) . In a study that was made in Casablanca Medical Faculty, Morocco, in total of 275 medical students the overall finding showed that approximately 52% of the students were stressed by examinations, and the fifth year medical students showed the highest stress prevalence with no difference between female and male students (17) . In Libya a study was done and suggested that stress management and relaxation programs must be offered on campus to prevent stress-related symptoms.…”
mentioning
confidence: 99%